Electrodeposition of copper on titanium wires: Taguchi experimental design approach - Rosa, J. L.; Robin, A.; Silva, M. B. [UNESP]; Baldan, C. A.; Peres, M. P. [UNESP] (Elsevier B.V. Sa, 2009)
Electrodeposition of thin copper layer was carried out on titanium wires in acidic sulphate bath. The influence of titanium surface preparation, cathodic current density, copper sulphate and sulphuric acid concentrations, electrical charge density and stirring of the solution on the adhesion of the electrodeposits was studied using the Taguchi statistical method. A L(16) orthogonal array with the six factors of control at two levels each and three interactions was employed. The analysis of variance of the mean adhesion response and signal-to-noise ratio showed the great influence of cathodic current density on adhesion. on the contrary, the other factors as well as the three investigated interactions revealed low or no significant effect. From this study optimized electrolysis conditions were defined. The copper electrocoating improved the electrical conductivity of the titanium wire. This shows that copper electrocoated titanium wires could be employed for both electrical purpose and mechanical reinforcement in superconducting magnets. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Titanium; Copper; Electroplating; Adhesion; Taguchi method; Superconducting magnet